Blueprint : Go rider (smart apps) / Cik Muhamad Zafri Che Sabudin, - Che Sabudin, Cik Muhamad Zafri; Zulkafli, Muhammad Nazmi; Abdullah, Azrul Hakimi; Hashim, Mohamad Hasif; Hashim, Addam (2019)
Go Rider Ltd is a new company providing transportation services through our company application. The services can be directly provided by our company, or it can be anyone who own a motorcycle and leveraging their motorcycle to provide the transport services to the customer. The decision to choose this type of service has gone through many difficulties and obstacles. After a long research and discussion among ourselves, we finally decided and agreed to proceed to do a blueprint project on product focusing mainly on Go Rider apps. The reason we choose Go Rider apps as a main product is because traffic congestion always been a problem to people in urban area during a peak hour. Therefore, we take this as opportunity to solve their problem in getting late to the office, work, or anywhere to their destination. We do our best to provide an efficient, affordable and friendly user app to serve our customer. The wide usage of smartphones among the community has made the process of distributing the apps existence easier and gone viral fasters than news.